Russian Collective Identity Construction in State Media During Russia’s Full-Scale Invasion of Ukraine (Global Media Journal - German Edition, 2024)
In the evolving landscape of communication technology, the interplay between media and collective identity becomes crucial due to its ability to shape the socio-political dynamics of nations. This article aims to address the role of collective identity construction in Russian state media, arguing that it is a highly manipulated process in the context of the Russian invasion of Ukraine that aims to shape the way the events are perceived by the Russian population. Through narrative analysis, the article aims to explore how the subject of Russian collective identity is constructed in the political talk show Evening with Vladimir Solovyov during the timeframe of one and a half years starting from the beginning of the full-scale war in Ukraine on February 24, 2022. The identified narratives constitute a complex structure that contributes to the construction of a particular Russian collective identity. While addressing different themes, overall, they shape public perceptions towards uniting individuals around particular ideas beneficial to the state and legitimising the actions of the Russian regime.
Keywords: Russische Medien; Agitainment; Talkshow Analyse; Staatspropaganda; kollektive Identität; Narrationsanalyse